Analisis Kelayakan Rencana Investasi Travel Baru Menggunakan Metode Hesitant Fuzzy Sets - Andreas Setijono; Yurida Ekawati (Universitas Bunda Mulia, 2019)
Transportation is a tool that supports the construction and economic development of a country. Because in this modern era, transportation provides easy access to the movement of goods and people from one place to another. This research was conducted at a company engaged in public transportation services. The main services provided are inter-city buses in the province, inter-city inter-provincial buses, tour buses and travel transportation. In 2018, the company has plans to add six travel vehicles and the capital owned is 500.000.000 Rupiah. While the remaining capital needed will be borrowed from Bank Antardaerah, so a business feasibility study is needed that can determine whether or not the investment plan is feasible. In addition, the Hesitant Fuzzy Sets method is used to model all forms of uncertainty that can cause losses. Hesitant Fuzzy Sets are an extension of the fuzzy set to handle inaccuracies where there are two or more sources of obscurity that appear simultaneously. Some basic methods used to determine the feasibility of investment plans are Payback Period (PP), Minimum Acceptable Rate of Return (MARR) and Internal Rate of Return (IRR). In addition, the Hesitant Fuzzy Sets method is used to model all forms of uncertainty that can cause losses. One example of such uncertainty is income uncertainty and expenditure uncertainty which are received by the company every year. The reason for using Hesitant Fuzzy Sets, because the method is an extension of the fuzzy set that can handle inaccuracies where there are two or more sources of obscurity that appear simultaneously.